Analysis Of The Inhibitory Ability Of Spike Attachment Of The Delta Variant Of Sars Cov-2 With Ace2 By The Active Compound In Turmeric (Curcuma longa L.) In Silico : Analisis Kemampuan Penghambatan Penempelan Spike Sars Cov-2 Varian Delta Dengan Ace2 Oleh Senyawa Aktif Pada Kunyit (Curcuma longa L.) Secara In Silico - Liyaajul, Pratasyah; Mushlih, Miftahul; Rini, Chylen Setiyo; Rohmah, Jamilatur (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
Turmeric (Curcuma longa L.) is an herbal plant that has many benefits as a treatment, including during the COVID-19 pandemic, one of the mechanisms of inhibition of SARS CoV-2 is to inhibit the attachment of ACE2 with Spike. The binding of the spike protein to the ACE2 receptor will produce conformational changes in the S protein, this study was conducted using an in silico method (computational analysis) which aims to determine the potential efficacy of Turmeric and its effectiveness in inhibiting the Delta variant of SARS CoV-2. The active compound contained in Turmeric (Curcuma longa L. ) obtained from the KNApSAcK database To determine compounds that can have potential and have good effectiveness in inhibition of the Delta Variant of SARS CoV-2, an analysis was carried out by looking at the binding energy and conformation changes that occur at the sticky point in each compound. Three-dimensional structure of SARS CoV-2 Varian Delta downloaded from the Protein Data Bank with PDB code 7V8B. Based on the analysis carried out, it was found that the compound (E)-nuciferoll has the lowest binding energy value of -1212.59 kcal / mol and is located at the initial attachment but cannot change the conformation, but from the sticky point of the compound (E)-nuciferol lies in the initial attachment of RBD-ACE2.